Mathematical Literacy in Terms of Cognitive Style With Pendidikan Matematika Realistik Indonesia Learning Assisted by Google Classroom (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aims to (1) find out the difference in the mean increase in students' mathematical literacy with Pendidikan Matematika Realistik Indonesia learning assisted by Google Classroom (PMRI-GC learning) and with Scientific learning, and (2) find out the effect of cognitive style on students' mathematical literacy with PMRI-GC learning. The design in this study was experimental designs: true experimental design: pretest-posttest control group design. The population in this study were students of class VIII SMP N 2 Wedi. The samples were determined by random sampling technique and determined that class VIIIA as the experimental class was given PMRI-GC learning and class VIIIB as the control class was given Scientific learning. The results of the study were the mean increase of students' mathematical literacy with PMRI-GC learning is better than students with scientific learning, the mean increase of students' mathematical literacy with PMRI-GC learning is in the medium category, while the mean increase of students' mathematical literacy with Scientific learning is in the low category, and there is an effect of cognitive style on mathematical literacy of students who receive PMRI-GC learning, with an effect of , meaning that cognitive style has an effect of on mathematical literacy.